The murine C'-terminally alternatively spliced form of p53 induces attenuated apoptosis in myeloid cells. - Almog, N (1997)
The onset of p53-dependent apoptosis results from the accumulation of damaged DNA. Recently, it was shown that the C' terminus of the p53 protein plays a central role in sensing damaged DNA. In our present study, we examined the role of the C' terminus in the induction of apoptosis. A temperature-sensitive (ts) mutant of the alternatively spliced form of p53 (p53AS-ts) and the ts mutant of the regularly spliced form (p53RS-ts) were used to generate series of stable clones with increasing amounts of p53 protein. Apoptotic patterns induced by either the regularly spliced p53 product (p53RS) or a C'-terminally alternatively spliced p53 product (p53AS) were compared. We found that although both forms of p53 induced apoptosis following expression of the wild-type protein conformation, the kinetics were different. Apoptosis induced by the p53AS protein was attenuated compared to that induced by p53RS. The delay in the manifestation of the apoptotic features following p53AS expression was in agreement with a delay in the regulation of the expression of apoptosis-related genes. The observation that p53 with an altered C' terminus is still capable of inducing apoptosis suggests that the actual onset of the apoptotic process most probably involves structural domains other than the C' terminus of the p53 molecule. However, the fact that the apoptotic activity mediated by the p53AS product was slower than that mediated by the p53RS product suggests that the C' terminus indeed exerts a certain control on the apoptotic activity of the p53 molecule.